A culture of collaboration: Forms and factors affecting collaboration between NESTs and NNESTs in extracurricular English activities - Grace Wivell (Indonesian JELT, 2020)
Fulbright English Teaching Assistants (ETAs) assist local English teachers to further the English language development of students around the globe, while simultaneously acting as cultural ambassadors for the United States. ETAs in Indonesia are required to spend between twenty and twenty-five hours each week in the classroom with their teaching counterpart(s) but are also encouraged to engage with their school and community outside of class, and as such many ETAs also spend considerable time developing extracurricular English programming. While some of these extracurriculars are facilitated independently by the ETAs, many are collaborative projects with counterparts from the host institution. As part of a larger five-year research plan initiated by the American Indonesian Exchange Foundation (AMINEF) that seeks to explore the impact of ETAs, this research explores the collaboration within these extracurriculars. It seeks to identify the forms that this collaboration takes, as well as the factors that affect the collaboration. The findings suggest that collaboration within these extracurriculars usually takes the form of either one teach – one assist model, or team teaching, and that logistical and interpersonal factors are of the greatest concern within the collaboration.